2014
DOI: 10.1136/archdischild-2014-306381
|View full text |Cite
|
Sign up to set email alerts
|

The effect of L-thyroxine treatment on left ventricular functions in children with subclinical hypothyroidism

Abstract: The results of this study showed that SH is associated with subclinical alterations in LV function, and LT4 replacement may improve LV systolic and diastolic parameters. However, since SH is usually a self-limiting process, these improvements in LV functions may simply be associated with the natural course of the disease and/or physiological linear growth of the children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 39 publications
0
19
3
Order By: Relevance
“…Moreover, recent longitudinal case-control studies demonstrated that untreated mild SH in children can be associated with early CV risk factors such as mild dyslipidemia, increased visceral adiposity, increased levels of homocysteine, early markers of endothelial dysfunction, and preclinical alteration in left ventricular function [94, 96, 101]. L-T4 treatment was associated with beneficial effects on most biochemical markers of CV risk and cardiac and endothelial function [96, 101]. …”
Section: Management Of Mild Sh In Childhoodmentioning
confidence: 99%
“…Moreover, recent longitudinal case-control studies demonstrated that untreated mild SH in children can be associated with early CV risk factors such as mild dyslipidemia, increased visceral adiposity, increased levels of homocysteine, early markers of endothelial dysfunction, and preclinical alteration in left ventricular function [94, 96, 101]. L-T4 treatment was associated with beneficial effects on most biochemical markers of CV risk and cardiac and endothelial function [96, 101]. …”
Section: Management Of Mild Sh In Childhoodmentioning
confidence: 99%
“…Only few studies have evaluated the effect of shortterm trials with L-T4 in heterogeneous populations of children with mild to severe SH (5,20,23), and none of them have focused on the relationship between SH and metabolic aspects.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of subclinical hypothyroidism on cardiac functions and Tissue Doppler Imaging parameters have www.nature.com/scientificreports/ mostly been reported in adult studies 10,11,15,16,18,[22][23][24] . Although the number of studies reporting on the cardiac effects of subclinical hypothyroidism have been growing recently, particularly in children, there is still scarcity in the number of studies conducted in children 9,25 . Left ventricle mass has been shown to increase in adults with subclinical hypothyroidism 11,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Rodonti et al 12 reported that left ventricular mass might increase in patients with thyroid stimulating hormone > 10 mU/l during long-term follow-up although no increase might be seen at baseline measurements. A review of the Englishlanguage literature showed that there have been only two studies reporting on increased left ventricular mass in children with subclinical hypothyroidism 9,26 . Of these, the study by Catli et al 9 evaluated 31 children with subclinical hypothyroidism and found a significant increase in left ventricular mass index and interventricular septal thickness.…”
Section: Discussionmentioning
confidence: 99%